Iron deficiency and early childhood caries: a systematic review and meta-analysis. Issue 23 (5th December 2021) - Ji, Shuai-Qi; Han, Rui; Huang, Ping-Ping; Wang, Shuang-Yi; Lin, Hao; Ma, Lei
Abstract : Supplemental Digital Content is available in the text Abstract: Backgrounds: Previous surveys have found that children with iron deficiency (ID) were likely to suffer from early childhood caries (ECC). We aimed to assess the scientific evidence about whether ID is intrinsically related to ECC. Methods: The medical subject headings (MeSH) terms and free words were searched on PubMed, Web of Science, Cochrane, China National Knowledge Infrastructure, Wanfang, and the Database for Chinese Technical Periodicals from March 2020 to September 2020. Two researchers independently screened the articles. Data extraction and cross-checking were performed for the studies that met the inclusion criteria. Meta-analysis was performed using the Cochrane Collaboration's Review Manager 5.3 software. Results: After excluding duplication and irrelevant literature, 12 case-control studies were included in the study. The meta-analysis demonstrated that children with ECC were more likely to have ID (odds ratio [OR] = 2.63, 95% confidence interval [CI]: [1.85, 3.73], P  < 0.001). There was no statistically significant association found between the level of serum ferritin and ECC (weighted mean difference (WMD) = −5.80, 95% CI: [−11.97, 0.37], P  = 0.07). Children with ECC were more likely to have iron-deficiency anemia (OR = 2.74, 95% CI: [2.41, 3.11], P  < 0.001). The hemoglobin (HGB) levels in the ECC group were significantly lower compared with that in the ECC-free group (WMD = −9.96, 95% CI: [−15.45, −4.46], P  = 0.0004). The mean corpuscular volume (MCV) levels in the ECC group were significantly lower compared with that in the ECC-free group (WMD = −3.72, 95% CI: [−6.65, −0.79], P  = 0.01). Conclusions: ID was more prevalent in children with ECC, and the markers of iron status in the ECC group, such as serum ferritin, HGB, and MCV, were relatively lower than the ECC-free group.